Assessing School Readiness for Social and Emotional Learning: A Study of School Leadership Perceptions and Attitudes - Elharati, Nahla (AUC Knowledge Fountain, 2026)
This study explores the integration of social and emotional learning (SEL) in a number of British schools across Egypt, focusing on how school leaders defined and perceived its importance in student development. Through in-depth interviews with twelve school leaders, this study found that school leaders’ definitions of SEL emphasized self- awareness, self-regulation, and relationship-building, alongside a strong focus on the real-life applicability of SEL both within school settings and in students’ future lives. School leaders also expressed positive attitudes toward the benefits of SEL, particularly its role in enhancing academic performance, promoting student well-being, improving peer relationships, and reducing bullying, contributing to a more positive school climate. However, SEL practices varied significantly across the participating schools. While some schools had integrated SEL into classroom instruction and across school practices, others implemented SEL only occasionally through annual events or on-demand interventions. The implementation of SEL faced systematic, cultural, institutional, training, and assessment challenges. These challenges, both individually and in their interconnectedness, hindered effective SEL integration. Participants identified several key facilitators of effective SEL implementation, including targeted training, dedicated time allocation, and specific teacher attributes such as empathy, commitment, and a willingness to learn. Additionally, community influence was noted as an important factor, emphasizing the need for a multi-level approach to achieve maximum impact. Participants underscored the importance of raising awareness and advocating SEL and its benefits, beginning with school leadership but extending to all stakeholders. Ensuring cultural relevance and appropriateness of SEL practices was also highlighted as essential for successful implementation.